An Analysis of Pedagogical Course Learning Through Microsoft Teams Online Learning for Elementary School Teacher Education Students - Kuswaty, Maya; Suhadah (KRAKATAU (Indonesian of Multidisciplinary Journals), 2024)
This study analyzes the effectiveness of learning Pedagogy courses through the Microsoft Teams online platform for students of the Elementary School Teacher Education Study Program (PGSD). Qualitative research methods are used to gain in-depth insights into students' experiences and challenges faced during the online learning process. Data were collected through in-depth interviews with 15 students and document analysis covering learning activities for one semester. The results of the study indicate that Microsoft Teams provides flexibility of time and easy access to lecture materials, as well as supports interaction and collaboration through video conference and chat features. However, students face challenges such as technical problems, device limitations, and lack of social interaction and direct support that affect understanding of the material. This study recommends improving technical support and infrastructure and developing more adaptive teaching strategies to address existing shortcomings. These findings provide valuable insights for the development and implementation of online learning technologies in the context of higher education, as well as providing a basis for further research in this area.